Efek Farmakologi Infusa Biji Melinjo (Gnetum gnemon L.) Sebagai Antihiperglikemia pada Mencit (Mus musculus) yang Diinduksi Dextrosa Monohidrat 40% - Feri Ira W(, Cita Dwi; NHS, Cikra Ikhda (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2015)
Diabetes mellitus is a group of disorders in which the body's carbohydrates, fats, and proteins metabolism was disordered and it has many other causes. This study objectives was to determine the pharmacological effects of melinjo infusion in decreasing blood glucose levels in mice (Mus musculus). This study using mice (Mus musculus) aged 2-3 months, 20 grams body weight. A total of 12 mice were divided into 4 groups, each was given dextrose monohydrate 40%. Group I as a negative control (CMC Na 1%), group II as positive control (glibenclamide), group III (melinjo infusion 25% w/v ) and group IV (melinjo infusion 50% w/v). The data obtained from the examination of blood glucose levels for 24 hours with an interval of 6 hours. Melinjo (Gnetum gnemon L.) infusion dose that can lower blood glucose levels in hyperglycemic mice is 50%. Repeated analysis of the data was done using ANOVA Duncan's test. The results showed that the dose 50% of infusion melinjo have a pharmacological effect in decreasing blood glucose levels by 33,41% and it was different significantly (p>0.01) compared to glibenclamide.